Pro Spring 2.5 - Machacek, Jan 1979- (Apress, 2005)
This resource brings J2EE/Java EE down to Earth for users who need to build lighter, better-performing agile enterprise Java-based applications using Spring Framework 2. The Spring framework can also integrate other noteworthy and hot open source tools like Apache Struts, Hibernate, OpenJPA, and GlassFish.
Print version record
Keywords: Java (Computer program language); Application software -- Development; Java (Langage de programmation); Logiciels d'application; Développement; COMPUTERS; Programming Languages; C♯; COMPUTERS; Programming Languages; Java; COMPUTERS; Programming Languages; Pascal; Application software; Development; Informatique